Atomic-scale modeling of the dissolution of oxidized platinum nanoparticles in an explicit water environment. Issue 13 (13th March 2023) - Slapikas, Robert E.; Dabo, Ismaila; Sinnott, Susan B.
Abstract : Pt nanoparticles (NPs) are currently being investigated for use in fuel cells: however, Pt NP oxidation and Pt atom dissolution as a function of size morphology and temperature is not well understood or currently quantified. Abstract : Pt nanoparticles (NPs) are currently being investigated for use in fuel cells; however, Pt NP oxidation as a function of size, morphology, and temperature is not well understood or currently quantified. In this study, the stability and dissolution of oxidized platinum NPs is examined via classical molecular dynamics in an explicit water environment. The NPs considered range in size from 1.35 to 2.92 nm in diameter and included five different monolayer (ML) coverages of O*. The simulations were performed at 300, 450, and 600 K with the many-body, reactive third-generation charge-optimized many-body or COMB3 potentials and examine the kinetics of NP dissolution in water. The Pt–O layer, which reduces the kinetic activity for Pt atom dissolution, is projected to make dissolution more favorable for O* MLs smaller than 0.5. The simulations further indicate that the Pt NPs' kinetic rates of dissolution are slowed by an increase in the number of adsorbed species caused by the dissociation of water molecules at the reconstructed facets of the Pt NPs. These findings quantify the effect of oxygen and temperature on the stability and dissolution of oxidized platinum NP in an explicit water environment similar to the conditions in fuel cells and electrocatalysis.